Frequencies of Phonemes in the General British and General American Accents of English: Literature Review and New Estimates - Gonzales Iturri, Andrei; Brooks, Greg; Baycroft, Bernard; Cochrane, Gill (Forum for Linguistic Studies, 2025)
This article analyses the frequency of phonemes in the General British (GB) and General American (GA) accents of English in their contemporary forms in adult usage. Part One presents a critical analysis of previous data on British and American accents, much of which data are phonetically deficient. We reveal the absence of any phonetically rigorous analysis of the GA accent. Part Three presents a thorough new analysis of the frequency of phonemes in GB and GA based on the Corpus of Contemporary American English (COCA): a corpus containing over 1 billion words. The first 20,200 most frequently occurring words in COCA were transformed into iteratively justified International Phonetic Alphabet (IPA) transcriptions in both accents. Results are shown for both lexical frequencies and text frequencies and for analyses based on the first 1000, 2000, 3000 and 4000 most frequent words in COCA. The analyses of both frequency types in both accents provide a much-needed source of up-to-date information about English language usage that fills critical accent inventory lacunae. The data will enable literacy scheme designers and practitioners involved in teaching English as an additional language to optimise the structure of their programmes to ensure learners access the most productive phonemes at the earliest juncture. Those working within the field of assistive technology and other emerging speech-communication technologies will also benefit from access to this contemporary catalogue of the GA and GB accents.